Efforts To Prevent Corruption Criminal Acts Carried Out By The Prabumulih City Government - Layaali, Khairul; Maroni, Maroni; Farid, Muhammad (Universitas Dehasen Bengkulu, 2024)
Corruption is one of the serious challenges facing Indonesia, with widespread impacts on various aspects, including the economy, social life, and the level of public trust in the government. To overcome this problem, various regulations have been issued and eradication efforts continue to be carried out, involving the active role of the government and law enforcement officers. This study uses two approaches, namely the normative legal approach and the empirical legal approach. The data collected include primary data, obtained through interviews with respondents related to the subject matter of this thesis, as well as secondary data taken from literature studies. Data analysis was carried out qualitatively. The results and discussion of the study show that the Prabumulih City Government through the Regional Inspectorate has shown commitment in efforts to prevent corruption by implementing the principles of good governance, transparency, and accountability.